Free margin length and geometric height in aortic root dilatation and leaflet prolapse: implications for aortic valve repair surgery. (14th May 2019) - Tamer, Saadallah; Mastrobuoni, Stefano; van Dyck, Michel; Navarra, Emiliano; Bollen, Xavier; Poncelet, Alain; Noirhomme, Philippe; Astarci, Parla; El Khoury, Gebrine; de Kerchove, Laurent
Abstract: OBJECTIVES: Our goal was to assess the aortic leaflet free margin length (FML) and geometric height (gH) in a normal aortic valve (AV), aorta dilatation and aortic leaflet prolapse. METHODS: We measured the FML and gH intraoperatively in 132 patients operated on for aortic insufficiency, aortic dilatation, endocarditis or fibroelastoma. Patients were divided into 3 groups: normal tricuspid AV (group 1, n = 12), aortic dilatation (group 2, tricuspid = 43, bicuspid = 18) and leaflet prolapse (group 3, tricuspid = 32, bicuspid = 27). The FML and gH were compared between the groups and between the leaflets within each group. RESULTS: In a normal tricuspid AV, the mean FML and gH were 34.7 ± 3.1 mm and 18.8 ± 1.7 mm, respectively. In group 2 tricuspid, the FML and gH were greater than those in group 1 (FML 43.7 ± 4.4, P < 0.001; gH 21.2 ± 1.8, P = 0.003). In group 3, tricuspid, the FML of the prolapsing leaflet was greater than the FML of the non-prolapsing leaflet (48.3 ± 5.4 vs 42.2 ± 3.6; P < 0.001). In group 2, bicuspid, FML of both leaflets were similar in group 2, but augmented on the fused leaflet compared to the non-fused leaflet in group 3 (fused 55.4 ± 6.3; non-fused 46.2 ± 6.2; P < 0.001). In groups 2 and 3 bicuspid, the gH of the non-fused leaflet was systematically greater than the fused leaflet (group 2 non-fused 24.6 ± 2.5 vs fused 20.4 ± 2.1; P < 0.001) CONCLUSIONS: In aortic dilatation and leaflet prolapse, FML and, to a lesser extent, gH increased significantly compared to those of normal AV function. FML and gH dimensions also depended on the valve configuration (tricuspid/bicuspid). These data provide new insight into the pathomorphology of AV disease and will serve to further develop new methods of AV repair based on intraoperative measurements of the FML.